CALS-MODEL FOR FORMING THE ANTI-CRISIS POTENTIAL OF CONSTRUCTION ENTERPRISES - Stetsenko, S.; Sorokina, L.; Goiko, A.; Tsyfra, T.; Bolila, N. (Scientific Journal of Astana IT University, 2020)
This paper considers the pecularities of the formation of econmic immunity of construction companies. A system has been proposed to improve the mechanisms of preventive protection and securement of enterprises from loss of viability and subsequent self-liquidation or bankruptcy, which allows effectively identifying existing risks and threats from micro-, meso- and macro-environments and responding to them with the preventive means through economic immunity. A new definition for the term «economic immunity» of the enterprise is proposed, which includes subsystems of monitoring, early detection of internal and external threats, assessment of the degree of danger (risks), defusion, elimination or neutralization, and formation of «memory» of the threat through a system of indicators. The differences of economic indicators of construction enterprises, which are characterized by different levels of the anti-crisis potential use, are studied, the five most significant indicators of the use of the anti-crisis potential are identified. The rules-conditions for determining the level of activation of anti-crisis opportunities and vulnerability of enterprises to threats for economic security are formulated. Methods of identification and control of the level of anticrisis potential use of the construction enterprise in the context of digital transformation which allows estimating quality and expediency of administrative actions are developed. The formation mechanism of the anti-crisis potential of the construction enterprise is developed. Its structure is defined, conceptual foundations of the integrated information system creation of the construction enterprise that should provide the possibility of interaction of various subsystems within the enterprise and the analysis of threats from interaction with various stakeholders are substantiated.